Cost–Utility Analysis of Magnetic Resonance Imaging Management of Patients with Acute Ischemic Stroke in a Spanish Hospital (2015)
Introduction: Stroke has a high rate of long-term disability and mortality and therefore has a significant economic impact. The objective of this study was to determine from a social perspective, the cost–utility of magnetic resonance imaging (MRI) compared to computed tomography (CT) as the first imaging test in acute ischemic stroke (AIS). Methods: A cost–utility analysis of MRI compared to CT as the first imaging test in AIS was performed. Economic evaluation data were obtained from a prospective study of patients with AIS ≤12 h from onset in one Spanish hospital. The measure of effectiveness was quality-adjusted life-years (QALYs) calculated from utilities of the modified Rankin Scale. Both hospital and post-discharge expenses were included in the costs. The incremental cost-effectiveness ratio (ICER) was calculated and sensitivity analysis was carried out. The costs were expressed in Euros at the 2004 exchange rate. Results: A total of 130 patients were analyzed. The first imaging test was CT in 87 patients and MRI in 43 patients. Baseline variables were similar in the two groups. The mean direct cost was €5830.63 for the CT group and €5692.95 for the MRI group (P = not significant). The ICER was €11,868.97/QALY. The results were sensitive when the indirect costs were included in the analysis. Conclusion: Total direct costs and QALYs were lower in the MRI group; however, this difference was not statistically significant. MRI was shown to be a cost-effective strategy for the first imaging test in AIS in 22% of the iterations according to the efficiency threshold in Spain. © 2015, The Author(s).